The COP9 Signalosome Regulates Autophagosome Maturation - Su, Huabo (2011)
BACKGROUND: Autophagy is essential to intracellular homeostasis and involved in the pathophysiology of a variety of diseases. Mechanisms regulating selective autophagy remain poorly understood. The COP9 signalosome (CSN) is a conserved protein complex consisting of 8 subunits (CSN1 through CSN8) and known to regulate the ubiquitin-proteasome system (UPS). However, it is unknown whether CSN plays a role in autophagy. METHODS AND RESULTS: Marked increases in LC3-II and p62 proteins were observed upon Csn8 depletion in the cardiomyocytes of mouse hearts with cardiomyocyte-restricted knockout of the gene encoding CSN subunit 8 (CR-Csn8KO). The increases in autophagosomes were confirmed by probing with GFP-LC3 and electron microscopy. Autophagic flux assessments revealed that defective autophagosome removal was the cause of autophagosome accumulation and occurred prior to a global UPS impairment in Csn8-deficient hearts. Analyzing the prevalence of different stages of autophagic vacuoles revealed defective autophagosome maturation. Down-regulation of Rab7 was found to strikingly co-localize with the autophagosome accumulation at the individual cardiomyocyte level. A significantly higher percent of cardiomyocytes with autophagosome accumulation underwent necrosis in CR-Csn8KO hearts. Chronic lysosomal inhibition with Chloroquine induced cardiomyocyte necrosis in mice. Rab7 knockdown impaired autophagosome maturation of non-selective and selective autophagy and exacerbated cell death induced by proteasome inhibition in cultured cardiomyocytes. CONCLUSIONS: (1): Csn8/CSN is a central regulator in not only the proteasomal proteolytic pathway but also selective autophagy; (2) likely through regulating the expression of Rab7, Csn8/CSN plays a critical role in autophagosome maturation; and (3) impaired autophagosome maturation causes cardiomyocytes to undergo necrosis.